The Role of the Proteasome in Platelet Function - El-Kadiry, Abed El-Hakim (Int J Mol Sci, 2021)
Platelets are megakaryocyte-derived acellular fragments prepped to maintain primary hemostasis and thrombosis by preserving vascular integrity. Although they lack nuclei, platelets harbor functional genomic mediators that bolster platelet activity in a signal-specific manner by performing limited de novo protein synthesis. Furthermore, despite their limited protein synthesis, platelets are equipped with multiple protein degradation mechanisms, such as the proteasome. In nucleated cells, the functions of the proteasome are well established and primarily include proteostasis among a myriad of other signaling processes. However, the role of proteasome-mediated protein degradation in platelets remains elusive. In this review article, we recapitulate the developing literature on the functions of the proteasome in platelets, discussing its emerging regulatory role in platelet viability and function and highlighting how its functional coupling with the transcription factor NF-κB constitutes a novel potential therapeutic target in atherothrombotic diseases.